Measuring the Social Component of Sustainable Development in the Cities. The Case of Medellín, Colombia - Ewelina Biczyńska (Barometr Regionalny)
Sustainable development is currently a very up-to-date topic, the understanding and use of which has now gone further from its initial — environmental association. This paper is focused on one of the “youngest” kinds of sustainable development which is social sustainability. Its key elements are social inclusiveness, equality, access to education, diversity and safety, as well as good social capital — among others. As the most vague and human-related kind of sustainable development, it causes discussions on its measurement and international comparability. The example of Medellín, a Colombian city awarded for its innovativeness, is presented to discuss social sustainability measurement on the city level. This example proves that social sustainability tools are most useful when related closely with the social policies, which at the city level is fully doable.